Using the galactose‐α‐1, 3‐galactose enzyme‐linked immunosorbent assay to predict anaphylaxis in response to cetuximab. Issue 11 (15th March 2016) - Weiss, Jared; Grilley Olson, Juneko; Deal, Allison Mary; Chera, Bhishamjit; Weissler, Mark; Murphy, Barbara A.; Hayes, David Neil; Gilbert, Jill
Abstract : BACKGROUND: Cetuximab is a monoclonal antibody against epidermal growth factor receptor with activity against head and neck cancer and colorectal cancer. Anaphylaxis in response to cetuximab is a significant clinical problem in the Southeastern United States with a grade 3/4 infusion reaction rate of 14%. Previous retrospective data have suggested that the presence of preformed immunoglobulin E antibodies against galactose‐α‐1, 3‐galactose in serum can predict anaphylaxis in response to cetuximab. METHODS: Sixty patients were prospectively screened as part of the entry criteria for a phase 2 study of neoadjuvant carboplatin, nab‐paclitaxel, and cetuximab. Patients were recruited at 2 academic medical centers known to have high anaphylaxis rates: the University of North Carolina and Vanderbilt. Only patients with a negative laboratory result were treated on the clinical protocol. RESULTS: No patient experienced anaphylaxis; the negative predictive value was thus 100%. Other than smoking history, the demographics were similar for assay‐positive subjects and assay‐negative subjects. CONCLUSIONS: Subjects with a negative test result can be safely treated with cetuximab. Further research is required regarding the optimal cutoff for positivity and the positive predictive value. Cancer 2016;122:1697‐701 . © 2016 American Cancer Society . Abstract : Cetuximab is a monoclonal antibody with activity against head and neck cancer and colorectal cancer and has a 14% anaphylaxis rate in the Southeastern United States. In this phase 2 study of a cetuximab‐containing regimen, the negative predictive value of the galactose‐α‐1, 3‐galactose enzyme‐linked immunosorbent assay for anaphylaxis is 100%.